2015
DOI: 10.1007/s00404-015-3763-5
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of sublingual misoprostol and intramuscular oxytocin for prevention of postpartum hemorrhage

Abstract: Sublingual misoprostol is as effective as intramuscular oxytocin as a prophylactic oxytocic in the active management of third stage of labor for prevention of postpartum hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Priya in her study reported that two cases in misoprostol group and three cases in oxytocin group required additional oxytocin because of uterine atony. 22 Chaudhuri et al, in his study reported no statistical significance in the requirement of additional oxytocin in between the two groups in both the studies. 21 In Bellad et al study, one case in misoprostol group required additional oxytocin whereas 8 cases in oxytocin group which was statistically significant (p=0.002).…”
Section: Discussionmentioning
confidence: 82%
“…Priya in her study reported that two cases in misoprostol group and three cases in oxytocin group required additional oxytocin because of uterine atony. 22 Chaudhuri et al, in his study reported no statistical significance in the requirement of additional oxytocin in between the two groups in both the studies. 21 In Bellad et al study, one case in misoprostol group required additional oxytocin whereas 8 cases in oxytocin group which was statistically significant (p=0.002).…”
Section: Discussionmentioning
confidence: 82%
“…[30,38] Results from this scoping review also demonstrate the possibility and benefits of distribution of misoprostol to clients either for auto-administration, or administration by community health care professionals, auxiliary midwives or community health workers. [33,34,36,38,39,44,47,53,54] A study conducted in Rwanda [34] to investigate the coverage, acceptability, and feasibility of a program for PPH prevention at community and health facility level found that administration of misoprostol by CHWs at the time of delivery for home births achieved reasonable uterotonic coverage. On the other hand, the program achieved satisfactory uterotonic coverage of 82.5% for all deliveries at the level of health facility due primarily to routine and proper management of the third stage of labor for a high proportion of facility-based deliveries.…”
Section: Risk Factors For Pph Among Childbearing Womenmentioning
confidence: 99%
“…The risk of bias was assessed independently by LH and AW for 14 trials [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Six assessments [24][25][26][27][28][29] were produced during a review by Gallos et al [30].…”
Section: Risk Of Bias Of Included Trialsmentioning
confidence: 99%
“…Four trials were considered to have an unclear risk of selection bias as the methods to describe adequate random sequence generation were not reported or inadequately described [14,15,28,42]. There was an unclear risk for five trials [19,28,29,35,39] concerning allocation concealment as it was not reported appropriately. The Diop 2016 [11] and Raghavan 2015 [21] trials were cluster randomised trials meaning allocation would have been known in advance so were judged to be high risk for inadequate allocation concealment.…”
Section: Risk Of Bias Of Included Trialsmentioning
confidence: 99%
See 1 more Smart Citation